IMPLEMENTASI JSON VOLLEY PADA LOGIN PAGE UNTUK AUTENTIKASI USER PADA APLIKASI MOBILE - Zekson Arizona Matondang; Andy Syahputra Bukit (UPPM, 2020)
The development of mobile at this time has experienced developments in various circles, especially in Indonesia. This research focuses on how to make an application for user authentication on the login page on an Android Smartphone, by retrieving user data that has been registered in the database, using HTTP Connection and JSON Volley methods. Creating applications using the Java programming language with the help of the Eclipse IDE and MySQL for database server tools. In this study, the Application Program Interface (API) is a collection of PHP source code, the contents of which are a query to retrieve data from the database and will be coded into the JSON Form.